A Study on Mechanical Behaviours of Strapping Tapes Made from Polypropylene - Scrap - Moocharoen, Weerasak (Frontiers in Engineering Innovation Research, 2003)
The objective of this study on Polypropylene - recycling is to try to use all industrial scrap (no mixing with the virgin plastic). The Polypropylene-scraps that used in this work have been brought from the Textile factory (woven sack). The procedure will start with granulation, testing mechanical properties such as melt flow index, viscosity, modification with additives, finding of process-condition and comparative testing for tension and scratching resistances with standard goods. This research work will deal with the plastic (strapping tape) which is employed in the factory. Finally, it is expected that the result obtained will be used for reducing the factory cost and use recycled plastics.